Traditional treatments for treating lengkauk disease employed by the community in the Segedong Sub-district, Mempawah District, West Kalimantan Province, Indonesia - RUQIAH GANDA PUTRI PANJAITAN; DESTI RAHMADANI; HAYATUL FAJRI; DIAN AKBARINI; ZHU CAIPING (Society for Indonesian Biodiversity, 2025)
Abstract. Panjaitan RGP, Rahmadani D, Fajri H, Akbarini D, Caiping Z. 2025. Traditional treatments for treating lengkauk disease employed by the community in the Segedong Sub-district, Mempawah District, West Kalimantan Province, Indonesia. Biodiversitas 26: 94-101. Lengkauk is an illness that affects children, resulting in symptoms such as weight loss, abdominal bloating, frequent fever, irritability, lethargy and weakness. Other characteristics include pale palms, soles and face, stunted growth and decreased appetite. The use of plants as traditional medicine for treating lengkauk in children in the Segedong Sub-district, Mempawah, West Kalimantan, Indonesia is still practiced by the local community, although this knowledge is primarily held by certain elderly individuals, such as local shamans and midwives. This study aimed to identify the types of plants used, the parts of the plants employed, the preparation methods and the treatment practices for managing lengkauk. A qualitative research methodology was utilized with data collection conducted through triangulation techniques including interviews, observations and documentation. The research identified six types of plants used to treat lengkauk (i) bawang merah (Allium cepa); (ii) jengkol (Archidendron jiringa); (iii) kelapa hijau (Cocos nucifera); (iv) lempuyang (Zingiber zerumbet); (v) moje (Barleria cristata); and (vi) sirih hijau). The parts of the plants used include leaves, bulbs, fruits and rhizomes. These six plants belong to different families: Acanthaceae (B. cristata), Amaryllidaceae (A. cepa), Arecaceae (C. nucifera), Fabaceae (A. jiringa), Piperaceae (P. betle) and Zingiberaceae (Z. zerumbet).